Knitless : 50 no-knit, stash-busting yarn projects - McFadden, Laura (Running Press, a member of the Perseus Books Group, 2015)
"Are you a knitter, crocheter, crafter, or none of the above? This clever book gives yarn lovers--both knitters and non-knitters alike--50 fun ways to use their stashes without taking out their knitting needles. The projects are easy and simple, but with a modern aesthetic that manages to be both sophisticated and inviting. Get your hot glue gun fired up, adhere some pompoms to an old office chair, and make the most ho-hum seat in your house into a cozy piece of pop art furniture. Or treat your neck to a stylish infinity scarf. All you need is some bulky yarn and the ability to braid. This book will strike a chord with DIYers who love yarn but don't always want to take the time and effort to knit something from it. Projects also include a Sputnik lamp shade, a welcome mat, friendship bracelets, and even a rehabbed woven lawn chair. Put away your needles and crochet hooks and create fabulous projects, from accessories to home goods and more!"--Book cover flap.